1998
DOI: 10.1159/000018621
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Pancreatic Metastases from Renal Cell Carcinomas

Abstract: Pancreatic metastases from a renal cell carcinoma are rare and may occur long after manifestation of the primary disease. Resection of the metastases should be regarded as the best treatment. In our center, owing to the slow evolution of these secondaries, we perform resections capable of limiting the destruction of the pancreatic parenchyma as far as possible. The use of ‘atypical’ resections of the pancreas is characterized by a higher incidence of postoperative complications, particularly fistulas. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 16 publications
0
20
0
8
Order By: Relevance
“…Their frequency at autopsy in patients with malignant neoplasms is variable from 3 to 10.6% [3,4]. In the clinical settings their incidence is lower: in the study of Roland and van Heerden [1] of 1,357 patients who had undergone surgical resection for primary malignant tumors of the pancreas, it did not exceed 2% of cases; Butturini et al [5] among 304 pancreatic cancers described 5 cases (1.6%) of pancreatic metastases; Faure et al [6] among 269 pancreatic resections for cancer reported 8 of them (3%). In our experience of 708 cases of pancreatic tumors we found 3 cases (0.4%) of pancreatic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Their frequency at autopsy in patients with malignant neoplasms is variable from 3 to 10.6% [3,4]. In the clinical settings their incidence is lower: in the study of Roland and van Heerden [1] of 1,357 patients who had undergone surgical resection for primary malignant tumors of the pancreas, it did not exceed 2% of cases; Butturini et al [5] among 304 pancreatic cancers described 5 cases (1.6%) of pancreatic metastases; Faure et al [6] among 269 pancreatic resections for cancer reported 8 of them (3%). In our experience of 708 cases of pancreatic tumors we found 3 cases (0.4%) of pancreatic metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Only six of the mentioned studies obtained complete information on the extrapancreatic metastases during the entire course of disease (28)(29)(30)(31)(32)37). In five publications comprising 65 patients, 7 patients could be identified also having thyroid metastases leading to the coincidence rate of 11% (26)(27)(28)32,37). Yet, no study on the thyroid or pancreatic metastases of RCC reports such a high coincidence up to date.…”
mentioning
confidence: 99%
“…The pancreas is a rare site of metastasis from other malignant tumors, accounting for 0.4% to 3.0% of surgically operated pancreatic tumors [3][4][5][6]. Primary tumors metastasizing to the pancreas include RCC (with a prevalence of 45%) and, more rarely, lung carcinoma (15%), breast carcinoma (8%), and colon carcinoma (7%) [6].…”
mentioning
confidence: 99%